#TITLE_ALTERNATIVE# - MARAS NURUL KHAMSAH (NIM : 13205023), NOVA
Fractal is an irregular curve or a pattern which a small part from it has similar shape with the other parts or the bigger part or even with the original one. In this final project, fractal is implemented to design a multiband antenna. A Koch curve shape which is chosen in the antenna design, is implemented in two different form, they are in two dimensional and in three dimensional forms. The twodimensional form is called Koch modification gasket antenna, and the three dimensional form is called Koch modification conical antenna. Both form were designed to see the impact on several antenna properties such as refflection coefficient, radiation pattern, and currents distribution as well. From the simulation and measurement result of Koch modification gasket antenna, it shows that this antenna has better performance in radiation pattern especially in = 90⁰ plane, than that of Sierpinski gasket antenna. Simulation result of Koch modification conical antenna, shows that the performance of antenna has improved in radiation pattern, where there are no differences in maximum and minimum radiation level at horizontal plane for each of resonant frequencies than that of Koch modification gasket antenna which has differences in each of its resonant frequencies, like the difference of radiation level in first frequency is 1.02, in the second frequency is 7.53, and in the third frequency is 36. In conclusion, the three dimensional form of fractal antenna make an improvement in antenna performance.